A proposition for a multilateral carbon tax treaty - Falcão, Tatiana (Doctoral series, 2019)
This book proposes a multilateral framework through which countries may tax mineral resources (oil, gas and coal) and capture the full polluting potential of those energy resources through the tax. The framework is designed so that the tax is only levied once through the mineral resources' production chain. A compensation mechanism is proposed to account for non-combusted carbon by-products. The book thus addresses the following issues: - which type of tax is the most appropriate to capture oil, gas and coal's polluting ability; - what the best framework is to propose a multilateral environmental tax; - what the best legal instrument is to support an environmental tax applied under the defined terms; - the compatibility of the proposed tax with international trade regulations; and - which is the most suitable intergovernmental organization to host the legal instrument and to administer the aforementioned tax. The research draws from the existing principles of environmental regulations and international environmental agreements (such as the UN Framework Convention on Climate Change, the Kyoto Protocol and the Paris Agreement) to place the proposed Multilateral Carbon Tax Treaty within the framework of environmental protection and establish a dialogue between the environmental legal framework and the proposed tax instrument of resource mobilization. The book further explains why the Paris Agreement has provided the international community with the right momentum for a new tax framework to be adopted within the dual context of tax and environmental law.